Students' Perceptions of Online Vertebrate Anatomy Practicum - Elania Zoela Saputri; Yunita Agustiani; Siti Faridah; Alifia Putri Ramadhani; Much. Fuad Saifuddin; Destri Ratna Ma'rifah (PAEDAGOGIA, 2022)
Practicum has an essential role in learning biology, especially during online learning. Various forms of online practicum are sought, one of which is in the vertebrate anatomy course practicum. As a form of evaluation, it is necessary to know student perceptions of the online practicum process. The purpose of the study was to determine the quality of the online practicum process for vertebrate anatomy courses based on the perceptions of students participating in the practicum. This research is qualitative descriptive research. The data collection instrument used a questionnaire containing 12 statement items with a Likert scale using five choices. The study involved 34 students of the 2020 Biology Education Study Program, FKIP UAD, who had completed the online practicum for the vertebrate anatomy course. The results showed that students' perceptions of understanding, aspects of practicum media, and aspects of the online practicum process for vertebrate anatomy courses gave a positive response. However, every aspect had to be improved again. The positive response of students' perceptions shows that the quality of the online practicum for the vertebrate anatomy course has met student expectations. Online practicums can be innovated to support the implementation of future practicums in conditions free from pandemics.